2014
DOI: 10.1159/000368152
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatocellular Carcinoma with Child-Pugh C Cirrhosis

Abstract: Background: In most guidelines, no other interventional therapy but liver transplantation is recommended for the treatment of hepatocellular carcinoma (HCC) with Child-Pugh C cirrhosis (CP-C). However, in Japan, patients were sometimes treated with expectation of benefit. Summary: A workshop was conducted to explore the state of treatments for CP-C HCC in Japan. After the workshop, a questionnaire on therapies was given to the panelists. Clinical data of 769 patients with CP-C HCC from 8 hospitals as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(24 reference statements)
1
12
1
Order By: Relevance
“…A follow-up survey by the Liver Cancer Study Group of Japan revealed that approximately half of Child-Pugh class C HCC patients in Japan receive locoregional therapy (resection, ablation, and TACE, or HAIC). Propensity score-matching analysis of data from this follow-up survey showed that local ablation therapies and TACE improve survival in patients with a Child-Pugh score of 10 or 11 [35], consistent with other multicenter or single-center studies [36][37][38][39]. In Japan, locoregional therapy is used in routine clinical practice for carefully selected patients with Child-Pugh C HCC within the Milan criteria, and TACE and ablation appear to be beneficial in such patients.…”
Section: Implications Of the Results Of The Gideon Studysupporting
confidence: 82%
“…A follow-up survey by the Liver Cancer Study Group of Japan revealed that approximately half of Child-Pugh class C HCC patients in Japan receive locoregional therapy (resection, ablation, and TACE, or HAIC). Propensity score-matching analysis of data from this follow-up survey showed that local ablation therapies and TACE improve survival in patients with a Child-Pugh score of 10 or 11 [35], consistent with other multicenter or single-center studies [36][37][38][39]. In Japan, locoregional therapy is used in routine clinical practice for carefully selected patients with Child-Pugh C HCC within the Milan criteria, and TACE and ablation appear to be beneficial in such patients.…”
Section: Implications Of the Results Of The Gideon Studysupporting
confidence: 82%
“…Nouso et al. also showed that TACE for HCC in Child–Pugh C patients provided a survival benefit, whereas local ablation or TAI did not . In the present cohort, there were no significant differences between the prognosis of patients treated with ablative therapies and those with TACE in the patients with up to 7 criteria and with total bilirubin of less than 3 mg/dL, and there was no certain conclusion of survival benefit from treatment against HCC in Child–Pugh C LC patients beyond up to 7 criteria with total bilirubin of less than 3 mg/dL because of their heterogeneous characteristics.…”
Section: Discussioncontrasting
confidence: 38%
“…It was reported that a high level of serum bilirubin (>3 mg/dL) was a prognostic factor shown in analyses of 157 Child–Pugh C patients with HCC . The average level of total bilirubin of the patients who were treated with some kind of method was 2.85 ± 1.9 mg/dL.…”
Section: Discussionmentioning
confidence: 98%
“…Experimental treatments for Child-Pugh C patients without hepatic encephalopathy or refractory ascites and with a serum bilirubin concentration ≤3 mg/dl include ablation and subsegmental TACE. Retrospective studies using propensity score matching [45,46,47] showed a survival benefit in patients with Child-Pugh score 10 or 11; however, there have been no randomized clinical trials. Further prospective clinical studies are needed to address this issue.…”
Section: Treatment Algorithm For Hcc Proposed By the Jshmentioning
confidence: 99%